Plan de negocio que permita la implementación del área de comercio internacional en la empresa Racores y Mangueras de Colombia S.A.S. (2019)
The growing demand of the country leads companies to internationalize, is the reason for this business plan, they are heading to the creation of an international trade area in the company Racores y Mangueras de Colombia S.A.S., current trading company of the Colombian East. Due to the number of references handled by the company in question, the study is focused on the Hydraulic Hoses, a good start because they represent one of the highest revenues for the Organization, which is why the study begins with a technical description of the hydraulic hoses to be commercialized, in order to improve the quality of the product, determining the profitability, the cost-benefit ratio and the opportunity to improve the profit margin of the company, to then go on to investigate the main procedures and import requirements for carrying out the activity, the most recommended incoterms and the correct handling of them.